COMPORTAMIENTOS RIESGOSOS ENTRE LOS JÓVENES: EL CASO DE LA ACTIVIDAD SEXUAL - Dussaillant L., Francisca (La Sociología en sus Escenarios, 2010)
<!–[if gte mso 9]> ceo_2010_1 12.00 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Abstract. This article of Francisca Dussaillant L. looks for to be a contribution to advance in the difficult objective to enter itself in the youthful mentality. Among others things, are tried to explain by means of econometric studies the sexual conduct of the adolescents and Chilean young people. According to Dussaillant little it has been written in Chile on the sexual customs of the young people, especially little has been written from a discipline like the economy. Nevertheless, the subject to try is very excellent: in Chile they are born every year more than 35 thousand children from adolescent mother (smaller of 20 years of age), which corresponds to around a 15% of the total of been born children. Many of these children of adolescent mothers are fruits of pregnancies no wished that a marriage or stable coexistence happens outside. It is common that the parents of these children are absent or little by little they are broken contact with the mother and his son. These mothers sometimes see in the maternity an opportunity to be realized and to grow in a relation of mutual affection with the boy. But in other occasions the mothers see truncated their projects of work or studies and see excessively made difficult of their way towards a stable and total adult life. Resumen. Este artículo de Francisca Dussaillant L. busca ser un aporte para avanzar en el difícil objetivo de adentrarse en la mentalidad juvenil. Entre otras cosas, se intenta explicar mediante estudios econométricos la conducta sexual de los adolescentes y jóvenes chilenos. Según Dussaillant poco se ha escrito en Chile sobre las costumbres sexuales de los jóvenes, especialmente poco se ha escrito desde una disciplina como la economía. Sin embargo, el tema a tratar es muy relevante: en Chile nacen todos los años más de 35 mil hijos de madre adolescente (menor de 20 años de edad), lo que corresponde a alrededor de un 15% del total de niños nacidos. Muchos de estos hijos de madres adolescentes son frutos de embarazos no deseados que ocurren fuera de un matrimonio o convivencia estable. Es común que los padres de estos niños estén ausentes o poco a poco se vayan desvinculando de la madre y su hijo. Estas madres en ocasiones ven en la maternidad una oportunidad para realizarse y crecer en una relación de mutuo cariño con el niño. Pero en otras ocasiones las madres ven truncados sus proyectos de trabajo o estudios y ven dificultado de sobremanera su camino hacia una vida adulta estable y plena.